Pengaruh Kompetensi Pegawai Terhadap Kualitas Pelayanan di Kecamatan Dumbo Raya Kota Gorontalo - Adam, Putri Angriani Sofia; Aneta, Yanti; Hamim, Udin (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the influence of employee competency on the quality of public services in Dumbo Raya District, Gorontalo City. The approach in this research is quantitative. The sample in this study was 105 people consisting of 93 members of the public and 12 employees. The type of data in this research is primary. The data collection technique is by distributing questionnaires. The data analysis technique uses simple linear regression. The results of this research show that employee competency has a positive and significant effect on the quality of public services at the Dumbo Raya District Office, Gorontalo City. Positive test results mean that the improvement in the quality of public services at the Dumbo Raya District Office, Gorontalo City occurs because employees have good competence in carrying out their mandated duties and responsibilities related to public, technical and administrative services. The influence of employee competency on the quality of public services is 69.00% while the remaining 31.00% is influenced by other variables not examined in this research, such as infrastructure and facilities variables, information systems and technology, policies and procedures, management of budget resources in service, openness and transparency, community participation, supervision, organizational culture as well as partnership and collaboration with the sub-district government.